Pengembangan Kapasitas Produksi dan Diversifikasi Produk Jamu Untuk Meningkatkan Daya Saing UMKM Di Gununggajah Kabupaten Klaten - Kusumandari, Rafika Bayu; Faturrohman, Hafidz; Kusumaningtyas, Natasya; Nisak, Siti Habibatun; Solikhah, Nuriana Putri (Welfare : Jurnal Pengabdian Masyarakat, 2024)
The development of production capacity and product diversification for herbal drinks (jamu) is crucial to enhance the competitiveness of micro, small, and medium enterprises (UMKM) in Gununggajah, Klaten Regency. This community service initiative was motivated by the potential of jamu as a traditional heritage product that can significantly contribute to local economic growth. However, the challenges faced by UMKM, including limited production skills, lack of innovation, and low market reach, hinder their competitiveness. The program aimed to empower local UMKM by improving production techniques, diversifying product variations, and strengthening branding strategies. The activities included training sessions, hands-on workshops, and mentoring in financial and digital marketing management. The results demonstrated increased production efficiency, the creation of innovative jamu products, and expanded market access for participating businesses. This initiative underscores the importance of continuous support for UMKM to foster sustainable economic development in rural areas.